Contracting frictions and inefficient layoffs of older workers - Martin Kerndler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In light of the low re-employment opportunities that workers above age 55 face in continental Europe, inefficient separations of older workers may generate a significant welfare loss for the economy. The economic literature therefore suggests eliminating any governmental policies that distort firing and retirement decisions. In this paper, I argue that even without any governmental distortions, there may still be inefficient destruction of older workers' jobs due to market-inherent contracting frictions that may arise due to asymmetric information. I demonstrate this in a two period model of the labor market where risk-averse workers choose their preferred wage contract from a restricted subset of the contract space. I find that an equilibrium with bilaterally inefficient layoffs of older workers emerges under certain conditions. These conditions are satisfied more easily if high outside options, such as early retirement benefits, become available for the elderly. This prediction is consistent with empirical studies postulating that generous social security systems increase the incidence of being 'pushed' into early retirement by the employer. On the other hand, training programs, wage subsidies, and employment protection are found to decrease the incidence of bilaterally inefficient layoffs.
Keywords: J14; J41; J63; 330